2004
DOI: 10.1038/sj.onc.1207419
|View full text |Cite
|
Sign up to set email alerts
|

A novel apoptotic pathway induced by the drs tumor suppressor gene

Abstract: The drs gene was originally isolated as a suppressor against v-src transformation. Expression of drs mRNA was markedly downregulated in a variety of human cancer cell lines and tissues, suggesting that the drs gene acts as a tumor suppressor. In this study, we found that ectopic expression of the Drs protein induced apoptosis in human cancer cell lines. Analyses using deletion mutants of drs revealed that both the C-terminal region and the three consensus repeats in the N-terminal region are essential for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 37 publications
0
42
1
Order By: Relevance
“…The deletion of these repeats apparently decreased apoptosis, indicating that sushi domains may be the key functional domains in apoptosis; however, the binding partners of sushi domain are unknown. Drs-induced apoptosis involved sequential activation of caspases 12, 9, and 3; however, neither cytochrome-c release nor activation of caspase 8 was observed, suggesting that mitochondrial pathway does not mediate drs-induced apoptosis (22). In contrast, in the present study, TMPS activated not only caspase 9 and 3 but also caspase 8, indicating that TMPSinduced apoptosis may involve the participation of various kinds of apoptotic pathways.…”
Section: Discussioncontrasting
confidence: 52%
“…The deletion of these repeats apparently decreased apoptosis, indicating that sushi domains may be the key functional domains in apoptosis; however, the binding partners of sushi domain are unknown. Drs-induced apoptosis involved sequential activation of caspases 12, 9, and 3; however, neither cytochrome-c release nor activation of caspase 8 was observed, suggesting that mitochondrial pathway does not mediate drs-induced apoptosis (22). In contrast, in the present study, TMPS activated not only caspase 9 and 3 but also caspase 8, indicating that TMPSinduced apoptosis may involve the participation of various kinds of apoptotic pathways.…”
Section: Discussioncontrasting
confidence: 52%
“…Tambe Y et al [7] also showed that the product of drs gene can interact with Nogo-B, and the coexpression of drs and Nogo-B can increase the efficiency of apoptosis. Previous experiments demonstrate that overexpressed Nogo-B protein induces apoptosis in various cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the 17 highly upregulated genes in the HGG-02 cells represent well accepted or potential tumor suppressors, including CDKN2A (35,36), TFAP2C (37), IGFBP3 (38), CDKN2B (36), FRZB (39), SRPX (40) and Siva1 (41). However, the downregulated genes involved genes associated with the ECM, including COL6A3, COL1A1, DCN, FN1 and FBN1.…”
Section: Discussionmentioning
confidence: 99%